Analisis Pemahaman Materi Bunyi dan Cahaya di Sekolah Dasar - Ariyadi, Daffa Harits; Rahmiyati, Ismi; Kusumaningrum, Kurnia Dewi; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article on sound and light aims to understand students about the nature, characteristics and behavior of sound and light. Primary goals include understanding sound and light waves, propagation, reflection, refraction, and interactions with matter. In addition, students are expected to be able to relate these concepts to everyday phenomena and technological applications. basic properties of sound and light as waves in the field of physics. Exploring the concepts of frequency, amplitude, and wave speed, this research illustrates the fundamental principles of both phenomena. Additionally, this article examines the complex interactions between sound and light, discussing their impact in the context of technology, art, and everyday applications. By detailing their scientific basis, this study aims to provide an in-depth understanding of these properties and illustrate the importance of sound and light in various aspects of our lives. Thus, it is hoped that this article will provide a better understanding of the interaction between sound and light, as well as provide insight into various practical applications involving these two phenomena.